Penerapan Algoritma Fisher Yates Shuffle pada Game Edukasi Pembelajaran Untuk Pendidikan Anak Usia Dini (PAUD) - Muhamad Ariandi; Muhammad Dwiki Ariyadi (Universitas Budi Darma, 2022)
Games can be used as educational tools, helping students learn about a particular subject or concept. Just like playing learning educational games for Early Childhood Education (PAUD), it can be a way to learn. In learning activities such as letters, numbers, colors, names of animals, plants, and so on, they still use conventional learning media, so they are less effective in implementing learning, where currently children interact more with smartphones than books, this can This causes parents whose children are still in elementary school, such as reading, counting, writing using books that are less attractive, which can cause children to be lazy to study, and less attractive to children in learning. From that problem, the author is interested in making educational game applications by utilizing smartphone media. And the application of this learning educational game was made by utilizing the Fisher Yates Shuffle Algorithm, by randomizing the questions in this application. Based on the test results, the implementation of the Fisher Yates Shuffle Algorithm for question randomization in the early childhood education learning educational game application (PAUD) went well, was in demand by PAUD children and there were no repeated questions that made PAUD children happier in study.